Preliminary Validation of the Defense and Veterans Pain Rating Scale (DVPRS) in a Military Population. Issue 1 (8th November 2012) - Buckenmaier, Chester C.; Galloway, Kevin T.; Polomano, Rosemary C.; McDuffie, Mary; Kwon, Nancy; Gallagher, Rollin M.
Abstract Background. The Army Surgeon General released the Pain Management Task Force final report in May 2010. Among military providers, concerns were raised that the standard numeric rating scale (NRS) for pain was inconsistently administered and of questionable clinical value. In response, the Defense and Veterans Pain Rating Scale (DVPRS) was developed. Methods. The instrument design integrates pain rating scale features to improve interpretability of incremental pain intensity levels, and to improve communication and documentation across all transitions of care. A convenience sample of 350 inpatient and outpatient active duty or retired military service members participated in the study at Walter Reed Army Medical Center. Participants completed the five‐item DVPRS—one pain intensity NRS with and without word descriptors presented in random order and four supplemental items measuring general activity, sleep, mood, and level of stress and the Brief Pain Inventory seven interference items. Using systematic sampling, a random sample was selected for a word descriptor validation procedure matching word phases to corresponding pain intensity on the NRS. Results. Parallel forms reliability and concurrent validity testing demonstrated a robust correlation. When the DVPRS was presented with the word descriptors first, the correlation between the two ratings was slightly higher, r = 0.929 (N = 171; P < 0.001), than ordering first without the descriptors, r = 0.882 (N = 177; P < 0.001). Intraclass correlation coefficient was 0.943 showing excellent alignment of word descriptors by respondents (N = 42), matching them correctly with pain level. Conclusions. The DVPRS tool demonstrated acceptable psychometric properties in a military population.